2020
DOI: 10.1021/acsanm.0c02457
|View full text |Cite
|
Sign up to set email alerts
|

Memory Devices via Unipolar Resistive Switching in Symmetric Organic–Inorganic Perovskite Nanoscale Heterolayers

Abstract: Organic–inorganic hybrid perovskite thin films with nanostructured polycrystalline grains have shown great potential in various nanoscale optoelectrical applications. Among them, the field of electrical memory has fallen behind due to insufficient knowledge of the related resistive switching characters and mechanisms. In the present work, switching behaviors of perovskite memory devices are systematically analyzed by comparing them with organic memory devices. We found that decreasing the conductivity of a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Moreover, EQE can still maintain >1% when the current density is as high as 600 mA/cm 2 . The turn-on voltage of our device is around 2.9 V. As for the “jump” at around 1 V in the I – V curve, and we attributed it to the unexpected microconducting channels, which has been reported in our previous work . Interestingly, the EL emission spectrum in Figure c shows only one peak at 546 nm with a full width at half maximum (FWHM) of 19.3 nm.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, EQE can still maintain >1% when the current density is as high as 600 mA/cm 2 . The turn-on voltage of our device is around 2.9 V. As for the “jump” at around 1 V in the I – V curve, and we attributed it to the unexpected microconducting channels, which has been reported in our previous work . Interestingly, the EL emission spectrum in Figure c shows only one peak at 546 nm with a full width at half maximum (FWHM) of 19.3 nm.…”
Section: Resultssupporting
confidence: 73%
“…The turn-on voltage of our device is around 2.9 V. As for the "jump" at around 1 V in the I−V curve, and we attributed it to the unexpected microconducting channels, which has been reported in our previous work. 45 Interestingly, the EL emission spectrum in Figure 3c shows only one peak at 546 nm with a full width at half maximum (FWHM) of 19.3 nm. It indicates that only large grains emit light under the condition of carrier injection only.…”
Section: Charge Transfer In Mixedmentioning
confidence: 97%
“…[1][2][3][4][5][6] Over the past decades the MHPs have emerged as suitable materials for solar cells, light emitting diodes, lasers, transistors, and memory devices. [7][8][9][10][11][12][13] It has been demonstrated that MHP-based photovoltaic devices show power conversion efficiencies of more than 22%, [14,15] and the devices can be produced on cheap non-crystalline substrates by both vapor deposition and solution processing. [8,11,16,17] Their excellent performance originates from the outstanding optoelectronic properties such as direct band-to-band recombination, long exciton diffusion length, high absorption coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…3D halide perovskites are the earliest and most commonly studied ones in the RS memory field since 2015. [69] So far, 3D perovskites have achieved extraordinary performance in memory applications, including a high ON/OFF ratio of 10 9 , [70] a small set/reset voltage of 0.1 V, [22] and a long retention time of over 10 5 s. [71,72] Unipolar, [73] bipolar, [74] and writeonce-read-many times (WORM) [75] switching types have been realized. Besides, due to their intrinsic photo-sensitive nature, 3D perovskites have been utilized in photonic memristors, which simultaneously respond to light illumination as another external stimulus in addition to the conventional electric bias.…”
Section: Introductionmentioning
confidence: 99%